Research in photography behind the image - Fox, Anna (Basics Creative Photography, 2021)
A body of photographic work is developed through knowledge gained in exploring the medium: investigating histories and theories of photography, observing the world, reading and listening, taking part in debate and critical reflection. With 150 images bringing together an eclectic range of photographic styles and genres, Fox and Caruana demonstrate how research can lead to fruitful, original photography projects.Designed to help you create better pictures, for portfolio or for profit, Research in Photography offers essential research and communication techniques to complement your technical expertise through a range of practical tools and examples. Two new chapters have been added to this second edition on'Writing for Research'and'Commercial Practice', as well as additional coverage discussing how to secure funding and professionalizing research.